Antiproliferation of Cryptocarya concinna-derived cryptocaryone against oral cancer cells involving apoptosis, oxidative stress, and DNA damage. Issue 1 (December 2016) - Chang, Hsun-Shuo; Tang, Jen-Yang; Yen, Ching-Yu; Huang, Hurng-Wern; Wu, Chang-Yi; Chung, Yi-An; Wang, Hui-Ru; Chen, Ih-Sheng; Huang, Ming-Yii; Chang, Hsueh-Wei
Abstract Background Cryptocarya -derived crude extracts and their compounds have been reported to have an antiproliferation effect on several types of cancers but their impact on oral cancer is less well understood. Methods We examined the cell proliferation effect and mechanism ofC. concinna -derived cryptocaryone (CPC) on oral cancer cells in terms of cell viability, apoptosis, reactive oxygen species (ROS), mitochondrial depolarization, and DNA damage. Results We found that CPC dose-responsively reduced cell viability of two types of oral cancer cells (Ca9-22 and CAL 27) in MTS assay. The CPC-induced dose-responsive apoptosis effects on Ca9-22 cells were confirmed by flow cytometry-based sub-G1 accumulation, annexin V staining, and pancaspase analyses. For oral cancer Ca9-22 cells, CPC also induced oxidative stress responses in terms of ROS generation and mitochondrial depolarization. Moreover, γH2AX flow cytometry showed DNA damage in CPC-treated Ca9-22 cells. CPC-induced cell responses in terms of cell viability, apoptosis, oxidative stress, and DNA damage were rescued by N-acetylcysteine pretreatment, suggesting that oxidative stress plays an important role in CPC-induced death of oral cancer cells. Conclusions CPC is a potential ROS-mediated natural product for anti-oral cancer therapy.